Effects of Nitrogen Application on Crop Production and Nitrogen Use in Rice–Wheat Rotation - Xiaohu Liu; Yulin Yang; Baohan Wu; Chenyang Lv; Huanhe Wei; Pinglei Gao; Hongcheng Zhang; Qigen Dai; Yinglong Chen (Agronomy)
In this study, a combined localization experiment was performed on different nitrogen application rates in rice–wheat rotation. Rice cultivar Nanjing 5718 and wheat variety Yangmai 25 were employed in this two-season study, with six and five distinct nitrogen rates designed during the rice and wheat growing seasons, respectively. Thus, a total of 30 N rate combinations were formed across the two seasons. Our findings indicate that when current-season N inputs ranged from 0 to 240 kg ha−1, residual N from the preceding season contributed significantly to yield improvement (5.58–18.96% increase) for subsequent crops, primarily through enhanced panicle formation and the number of grains per spike. Conversely, high current-season N rates (360–420 kg ha−1) lead to reduced yields (4.61–5.81%) in the following cropping cycle under identical N management practices. Maximizing annual crop production was achieved with a combined N regimen of 264.63 kg ha−1 (rice) and 254.89 kg ha−1 (wheat), yielding 14.21 t ha−1. Notably, current-season N levels exhibited significant correlations with starch and protein content in both rice and wheat, whereas previous-season N application showed no comparable relationships. Furthermore, soil N storage remained stable, and the highest N use efficiency was observed under the total annual N input of 547.7 kg ha−1 (rice + wheat).